Report on a visit to the Instituto de Investigaciones Tecnologicas and the Programa de Desarrollo y Diversificacion de Zonas cafeteras, Bogota 16-18 January, 1973 - Booth, RH; Wholey, D.W. (International Center for Tropical Agriculture, 1973)
Root storage: IIT offers laboratory analysis on reducing sugars and starch and an organoleptic panel for consumer acceptance studies. The Cafeteros offer a large supply of roots for further storage work, three farm sites to place the silos, and maketing outlets (already operating) to study transportation and marketing of stored roots. Storage of planting material: IIT offered useful information on techniques, additives and alternative waxing materials. The Cafeteros offered complete cooperation in obtaining data and performing experimental work on the farms under their jurisdiction. (AS)